Effect of nano zero-valent iron application on As, Cd, Pb, and Zn availability in the rhizosphere of metal(loid) contaminated soils - Vítková, Martina; Puschenreiter, Markus; Komárek, Michael (Chemosphere, 2018)
Characterisation of geochemical transformations and processes in soils with special focus on the rhizosphere is crucial for assessing metal(loid) bioavailability to plants during in situ immobilisation and phytostabilisation. In this study, the effects of nano zero-valent iron (nZVI) were investigated in terms of the immobilisation of As, Zn, Pb and Cd in two soil types and their potential uptake by plants using rhizobox experiments. Such system allowed monitoring the behaviour of trace elements in rooted and bulk soil compartments separately. Sunflower (Helianthus annuus L.) and ryegrass (Lolium perenne L.) were tested for As-rich (15.9 g As kg-1) and Zn-rich (4.1 g Zn kg-1) soil samples, respectively. The application of nZVI effectively lowered the uptake of all target risk elements into plant tissues. Efficient immobilisation of As was determined in the As-soil without a significant difference between plant and bulk soil compartments. Similarly, a significant decrease was determined for CaCl2-available fractions of Zn, Pb and Cd in nZVI-treated Zn-soil. The behaviour of As corresponded to changes in Eh, while Zn and Cd showed to be mainly pH-dependent. However, despite the observed stabilisation effect of nZVI, high amounts of As and Zn still remained available for plants. Furthermore, the accumulation of the target risk elements in roots and the overall effect of nZVI transformations in the rhizosphere were verified and visualised by SEM/EDS. The following immobilising mechanisms were suggested: (i) sorption onto both existing and newly formed Fe (hydr)oxides, (ii) formation of secondary Fe-As phases, and (iii) sorption onto Mn (hydr)oxides.
Keywords: Metals, Heavy; Lolium; látky znečišťující půdu; rhizosféra; Zinc; Trace Elements; Phytoremediation; Nanoparticles; biologická dostupnost; Environmental Restoration and Remediation; olovo; Redox; Helianthus; železo; Plant Roots; Lead; Arsenic; těžké kovy; znečištění životního prostředí; kořeny rostlin; Soil Pollutants; Environmental Pollution; Cadmium; Iron; jílek; Trace elements; kadmium; Rhizosphere; Soil stabilisation; zinek; regenerace a remediace životního prostředí; arsen; stopové prvky; Biological Availability